Drawing for Landscape Architecture : Sketch to Screen to Site - Hutchison, Edward (New York : Thames & Hudson Inc., 2011)
Combining traditional drawing techniques with those from CAD rendering, in nine chapters, "Drawing for Landscape Architecture" guides practitioners from their very first impression of a site, through concept and schematic design and client presentation to construction and site drawings, concluding with two case studies that show the final result.
Includes bibliographical references pages : 237
Keywords: Landscape architectural drawing; Landscape architecture -- Designs and plans